Additively manufactured Ti-6Al-4V replacement parts for military aircraft. (July 2019) - Jones, R.; Raman, R.K. Singh; Iliopoulos, A.P.; Michopoulos, J.G.; Phan, N.; Peng, D.
Abstract: This paper is motivated by the need to better understand the potential of Additively Manufactured (AM) Ti6-Al-4V replacement parts for future use on operational aircraft. Unfortunately, the interaction between surface and near surface (sub-surface) breaking material discontinuities, i.e. porosity due to and lack of fusion or keyholing, and the rough surface that is associated with AM parts complicates the analysis needed for certification. The present paper attempts to cut through this "Gordian knot". 1 To this end this paper presents a computational investigation into the fatigue life of AM Ti6-Al-4V parts subjected to two (quite different) representative flight load spectra that does not require the explicit modelling of the surface and subsurface porosity. Given the susceptibility of the "as manufactured" AM Ti6-Al-4V to fatigue crack nucleation and fleet experience from with conventionally manufactured parts, it is assumed that cracks in AM Ti6-Al-4V will initiate and grow from the day that the part enters service. The results of the present analysis suggest that for many parts of F/A-18 Classic Hornet and P3C (Orion) aircraft AM Ti-6Al-4V replacement parts may have an acceptable fatigue life. It also illustrates the potential for using fracture toughness measurements to guide the choice of the AM process and the associated post manufacture treatment.